2011
DOI: 10.1007/s12262-011-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Foreign Body in the Common Carotid Artery

Abstract: Penetrating trauma to neck resulting in arteriovenous (AV) fistula and aneurysms involving the carotid system are uncommon injuries with life-threatening consequences. We report here a case of a young factory worker who developed a traumatic AV fistula with false aneurysm, with however, no other complications. He was successfully operated when he presented to us two months after the injury and is doing well in follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Wulkan et al [3] reported complications associated with extraction of such foreign bodies due to internal maxillary artery injury, which can be surgically uncontrollable and potentially fatal [4]. Some delayed complications have also been reported like aneurysm [5] and erosion of the vessel wall [6]. Hence, imaging in the form of computed tomography scan is very important in these type of cases as routine x-ray usually misses out on vegetative foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Wulkan et al [3] reported complications associated with extraction of such foreign bodies due to internal maxillary artery injury, which can be surgically uncontrollable and potentially fatal [4]. Some delayed complications have also been reported like aneurysm [5] and erosion of the vessel wall [6]. Hence, imaging in the form of computed tomography scan is very important in these type of cases as routine x-ray usually misses out on vegetative foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Wulkan et al [3] reported complications associated with extraction of such foreign bodies due to internal maxillary artery injury, which can be surgically uncontrollable and potentially fatal [4]. Some delayed complications have also been reported like aneurysm [5] and erosion of the vessel wall [6]. Hence, imaging in the form of computed tomography scan is very important in these type of cases as routine x-ray usually misses out on vegetative foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Retained foreign material has been reported to be responsible for a number of late complications such as delayed aneurysm, [10] foreign body granulomas and reactions and migration with erosion of vessel walls. [11] Other reported late complications include cellulitis, abscess formation and discharging sinus.…”
Section: Discussionmentioning
confidence: 99%